Successful treatment of choreo-athetotic movements in a patient with an EEF1A2 gene variant - Eboni I Lance (SAGE Open Medical Case Reports, 2018)
Pathogenic variants in EEF1A2 , a gene encoding a eukaryotic translation elongation factor, have been previously reported in pediatric cases of epileptic encephalopathy and intellectual disability. We report a case of a 17-year-old male with a prior history of epilepsy, autism, intellectual disability, and the abrupt onset of choreo-athetotic movements. The patient was diagnosed with an EEF1A2 variant by whole exome sequencing. His movement disorder responded dramatically to treatment with tetrabenazine. To the best of our knowledge, this is the first report of successful treatment of a hyperkinetic movement disorder in the setting of EEF1A2 mutation. A trial with tetrabenazine should be considered in cases with significant choreoathetosis.